Construção e regulação do feminino no Almanaque de Farmácia D’a Saude da Mulher: análise de exemplares selecionados de 1930 a 1950 - Santos, Beatriz Oliveira (2019)
This research discusses aspects related to the construction and regulation of the female body from the analysis of the selection of 19 specimens of the pharmacy almanac entitled "The Health of Women" published from 1930 to 1950. This publication was one of the most read by the ladies between the beginning of the twentieth century until the mid-seventies and was the most popular medicine in the national industry focused on health. It showed ads of medicines, horoscopes, illustrations, phases of the moon, agricultural calendar, among other varieties. An analysis of the contents present in these publications was carried out in a constant dialogue with the reflections of authors who dealt with topics related to gender, power relations, health, among others. We present a brief history about the regulation and medicalization of the female body, especially from the nineteenth century, when it became, more strongly, the object of medicine intervention. We conceived the pharmacy almanacs as tools that may have contributed to the ideals of progress and civilization so much sought in the first decades of the twentieth century, especially in the two decades analyzed (1930 and 1940), when the country underwent a process of industrialization and aimed at sanitizing and discipline its citizens to the new times. We argue that women's almanacs, wrapped in moral discourses associated with the emerging values of modernity, may have acted as a pedagogical device, teaching, inspiring, regulating behaviors and modeling subjectivities, especially those of women subject to their influence. Such publications targeted especially the bourgeois ladies, urging them to be docile, good mothers, wives and caretakers of the home. We conclude that the almanacs played an expressive role as instruments of regulation, educating and medicalizing the female body, disseminating ideals of femininity / virility, family, health, hygiene and national progress. With this study, we hope to provoke critical reflections about deep-rooted social constructions about the feminine from the past to the present day.